2011
DOI: 10.1016/j.schres.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated illness in schizophrenia is not associated with 5-year brain volume change

Abstract: Although clinical outcome is associated with both brain volume (change) and DUI, we found no evidence for a relationship between DUI and brain volume (change). DUI and baseline brain volume or 5-year brain volume (change) seem to explain different parts of the variation in clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 74 publications
1
14
1
1
Order By: Relevance
“…Some studies have shown a relationship between antipsychotic medication use and longitudinal brain volume change in schizophrenia (Cahn et al 2002;Lieberman et al 2005), although others have failed to clearly demonstrate an influence of antipsychotic medication on brain volume change (Kasai et al 2003;Nakamura et al 2007;Crespo-Facorro et al 2008). Boonstra et al (2011) hypothesized that DUP, DUI or DPP, through their effect on outcome, might be associated with change in brain volume in schizophrenia, although these authors did not observe any significant association when studying the relationship between DUI and brain volume change. The majority of the patients had been taking only atypical antipsychotics during the follow-up but had switched their initially prescribed medication several times during the 3-year follow-up period ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies have shown a relationship between antipsychotic medication use and longitudinal brain volume change in schizophrenia (Cahn et al 2002;Lieberman et al 2005), although others have failed to clearly demonstrate an influence of antipsychotic medication on brain volume change (Kasai et al 2003;Nakamura et al 2007;Crespo-Facorro et al 2008). Boonstra et al (2011) hypothesized that DUP, DUI or DPP, through their effect on outcome, might be associated with change in brain volume in schizophrenia, although these authors did not observe any significant association when studying the relationship between DUI and brain volume change. The majority of the patients had been taking only atypical antipsychotics during the follow-up but had switched their initially prescribed medication several times during the 3-year follow-up period ).…”
Section: Discussionmentioning
confidence: 95%
“…The majority of the patients had been taking only atypical antipsychotics during the follow-up but had switched their initially prescribed medication several times during the 3-year follow-up period ). It has been suggested that the lack of association between those variables might be confounded by the use of antipsychotic medication (Boonstra et al 2011), given that it might cause either a decrease or an increase in brain volume change over time van Haren et al 2011). Differences in the methodology may also account for inconsistencies between investigations.…”
Section: Discussionmentioning
confidence: 99%
“…DUP has been found to be correlated with brain tissue volumes in some studies 8,83–86 but not in others. 44,45,87 Moreover, the direction of causality that underlies any association remains to be established because greater deficits in brain tissue volumes in those with greater DUP could reflect a more insidious onset of psychosis in those patients with greater longstanding deficits in brain tissue volumes. 84 Certainly, there has been no evidence to support the idea that longer DUP initiates a process of progressive and continuing brain change.…”
Section: The Search For Progressive Brain Changesmentioning
confidence: 99%
“…Duration of untreated psychosis at the time of the first entry into treatment was found to be unassociated with 5-year volume changes (Boonstra et al, 2011) While DUP was related to the severity of psychosis at baseline, intervening treatment events (including relapses) accounted for more variance in cortical atrophy over five years than did DUP. In terms of the clinical significance of these brain changes, van Haren et al (2011) demonstrated that the patients with the greatest cortical thinning over the 5-year follow-up period also had the worst five year functional outcomes.…”
Section: The Goal Of This Reviewmentioning
confidence: 99%